2008
DOI: 10.1007/bf03345650
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen inhibits transforming growth factor-α gene expression in human breast carcinoma samples treated with triiodothyronine

Abstract: We demonstrate that TGF-alpha mRNA expression is more efficiently upregulated by T3 than E2. Concomitant treatment with TAM had a mitigating effect on the T3 effect, while E2 induced TGF-alpha upregulation. Our findings show some similarities between primary culture and breast cancer cell lines, but also some important differences: a) induction of TGF-alpha, a mitogenic protein, by TAM; b) a differential effect of TAM that may depend on relative expression of ER alpha and beta; and c) supraphysiological doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
15
0
2
Order By: Relevance
“…In previous work, we demonstrated that TGFA expression increases after treatment with triiodothyronine (T 3 ) in MCF7 cells the same effect was observed in primary cultures [18,19].…”
Section: Introductionmentioning
confidence: 56%
“…In previous work, we demonstrated that TGFA expression increases after treatment with triiodothyronine (T 3 ) in MCF7 cells the same effect was observed in primary cultures [18,19].…”
Section: Introductionmentioning
confidence: 56%
“…Usando culturas primárias de CaM sob tratamen to com E2 e T3, identificamos uma expressão aumen tada de genes relacionados à evolução do ciclo celu lar (CLND1) e de aumento da atividade proliferativa (TGFA) em ambos os tratamentos (40). Em outro gru po de pacientes, as culturas primárias mostraram tam bém diminuição de TGFB1, relacionado a um efeito antiproliferativo, em ambos os tratamentos (39), repe tindo os resultados observados em linhagens MCF7, mas que não foram reproduzidos quando as linhagens não apresentavam o ER como a MDAMD231 (18).…”
Section: Resultsunclassified
“…Porém, quando o tratamento com TAM associado ao T3 foi empregado nas culturas primárias, observouse aumento da expressão de TGFA e diminuição da expressão de TGFB1, diferentemente das linhagens celulares (18,39,40).…”
Section: Resultsunclassified
“…The results showed that the modified oncolytic adenovirus can infect and replicate in breast cancer tissue slices, suggesting the great potential of this model for evaluating the potential of oncolytic adenovirus constructs (Pennington et al 2010). This list is not exhaustive and the literature shows that a lot of results were obtained by the slice culturing method, more particularly on the study of drugs effects like tamoxifen or paclitaxel (Conde et al 2008;Sonnenberg et al 2008;Rajendran et al 2011). Although used since the late 70's, the slice technique evolved over time and was adapted to technological innovations.…”
Section: Improving Representativeness Of the Model: Direct Culture Ofmentioning
confidence: 99%